Bio-activity of Xanthium strumarium extracts against tea mosquito bug, Helopeltis theivora - Sarmah, M.; Bhola, R.K. (Journal of Plantation Crops, 2014)
Laboratory and field experiments were conducted to study the antifeedant, repellent, ovicidal, longevity, anti-ovipositional properties and bio-efficacy of Xanthium strumarium extracts against adult tea mosquito bug, Helopeltis theivora. All the extracts exhibited significant bio-activity compared to control. The results were also compared with a commercial neem formulation, Azadirachtin. Among all the different solvent extracts, acetone extract recorded the highest antifeedant activity. The antifeedant activity possessed by this extract at 3 per cent concentration was significantly superior over azadirachtin at 5 per cent concentration. Fraction IV of silica gel column chromatography proved to be the most active fraction among those partitioned from the acetone extract by bioassay-guided separation. The extracts exhibited 86-99 per cent repellency at all tested concentrations. Fecundity, hatching of eggs and longevity of H. theivora were also significantly reduced with all the extracts, the highest being exhibited by the acetone extract. All the extracts exhibited promising bioactivity in reducing infestation of H. theivora in the field. Among all the tested extracts the acetone extract gave the highest significant efficacy.